MENGUNGKAP PANCASILA SEBAGAI PARADIGMA PENDIDIKAN AKUNTANSI INDONESIA - Zulkarim Salampessy (P3M Politeknik Negeri Ambon, 2024)
This research was conducted with the aim of revealing Pancasila as a paradigm of accounting education in Indonesia. This is a necessity where the national education system is based on Pancasila and UUD 1945. In this research, the author uses the Methodology of Wawasan Nusantara (MWN) and the Method of Kerakyatan with a conceptual approach. The objects of research are people who dedicate themselves to producing research works that are useful for many people. Research works that enlighten and inspire many people. Qualitative data on paradigms or world views, Pancasila as a paradigm, accounting education, ontology, epistemology, methodology, methods, axiology, and so on, which are sourced mainly from articles and books. The author collects the data using library techniques. Production of results and discussion using deductive techniques. The research results show that accounting education in Indonesia has the Pancasila paradigm as a broad world view, which includes ontology, epistemology, methodology, methods and axiology of accounting education. Keywords: Pancasila Paradigm, Ontology, Epistemology, Methodology, Method, Axiology, Accounting Education.